2021
DOI: 10.1007/s40670-021-01298-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval Practice for Improving Long-Term Retention in Anatomical Education: A Quasi-Experimental Study

Abstract: It is generally assumed by students that learning takes place during repeated episodes of rereading and rote memorization of course materials. Over the past few decades, however, research has increasingly indicated that the said notion can and should be enhanced with learning paradigms such as retrieval practice (RP). RP occurs when students practice retrieving their consolidated semantic memories by informally testing themselves. This strategy results in the re-encoding and re-consolidation of existing semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several students suggested that Fellows should engage students in quizzing exercises that require utilization of retrieval practices (RP) and other adult learning strategies 18 . Research performed by Azzam and Easteal 19 “demonstrated that participation in RP was associated with improved student performance on formal evaluations.” Their research, conducted in an anatomical education setting, “showed that RP enhances long‐term retention of semantic information, thereby improving learning.” 19 As such, it would be beneficial to incorporate this practice into laboratory sessions more frequently. Furthermore, quizzing in this fashion allows Fellows to tailor questions to students' current knowledge level.…”
Section: Discussionmentioning
confidence: 99%
“…Several students suggested that Fellows should engage students in quizzing exercises that require utilization of retrieval practices (RP) and other adult learning strategies 18 . Research performed by Azzam and Easteal 19 “demonstrated that participation in RP was associated with improved student performance on formal evaluations.” Their research, conducted in an anatomical education setting, “showed that RP enhances long‐term retention of semantic information, thereby improving learning.” 19 As such, it would be beneficial to incorporate this practice into laboratory sessions more frequently. Furthermore, quizzing in this fashion allows Fellows to tailor questions to students' current knowledge level.…”
Section: Discussionmentioning
confidence: 99%